Indonesian Marine Tourism: Developing a Favorable Tourism Destination to Attract International Sailors - Syafruddin Chan; Cut Aprilia; Zaida Rizki Zainul (Proceedings of AICS - Social Sciences, 2018)
This paper is to identify the Strength, Weakness, Opportunity, and Threat (SWOT) of Sailing Yacht tourism based on empirical evidence, mainly on demand aspects. The results will be very useful for decision-makers to design, launch and control marketing strategies and policies including promotional aspects to increase the awareness of the yacht sailors from various parts of the world, arouse their intention to come, increase spending and length of stay in Sabang as a free trade zone in west part of Indonesia. Data collection was conducted qualitatively by using Focus Group Discussion (FGD) technique conducted in 4 (four) sessions. Each session involves 10 (ten) sailors that serve as respondents. The data were then analyzed using both score and weight associated with IFAS and EFAS aspects. The output is mapped in Cartesian graphs. The finding of this study is that the strategy that must be implemented by Sabang is an Aggressive strategy, which uses the Strength to seize the profitable Opportunities. This is in line with the combined strategy that recommends Strength Opportunity (SO) as a priority strategy because it has the highest value of 16.92. In sequence, the next strategy is Weakness Opportunities (WO) that is to fix the Weakness in other to be able to grab the profitable Opportunities so that untapped opportunities can be utilized for the benefit of the sailors and tour operators. Then ST and WT strategies will be implemented to complete all 4 strategies recommended. With the implementation of these four strategies based on the priority scale, it is expected to maximize the utilization of limited resources, but also at the same time maximize the efforts made to achieve the goal of increasing the number of sailor visits to Sabang and increasing their length of stay.Keywords: yacht, marine tourism, Sabang, Phuket, Langkawi, travel destinations, sports tourism, Pulau Weh, marina.